Impact of fuelwood quality and quantity on rural households’ energy use in Omusati region in North-West of Namibia - Hainduwa, Feliciana Ndapewa (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScFor)--Stellenbosch University, 2013.